5‐Ethynyluridine: A Bio‐orthogonal Uridine Variant for mRNA‐Based Therapies and Vaccines. (31st January 2023) - Maassen, Sjors; Coenen, Britt; Dulk, Sara; van der Werff, Martijn; Warner, Harry; Spada, Fabio; Frischmuth, Thomas; Incarnato, Danny; van den Bogaart, Geert
Abstract: The identification of pseudo‐ and N 1 ‐methylpseudo‐uridine (Ψ and mΨ, respectively) as immunosilent uridine analogues has propelled the development of mRNA‐based vaccines and therapeutics. Here, we have characterised another uridine analogue, 5‐ethynyluridine (EU), which has an ethynyl moiety. We show that this uridine analogue does not cause immune activation in human macrophages, as it does not induce interleukin‐6 secretion or expression of the inflammatory and antiviral genes MX1, PKR, and TAP2 . Moreover, EU allows for prolonged expression, as shown with mRNA coding for yellow fluorescent protein (YFP). Side‐by‐side comparisons of EU with unmodified, Ψ, and mΨ revealed that EU‐modified mRNA is expressed at lower levels, but confers similar stability and low immunogenicity to the other uridine analogues. Furthermore, structure analysis of modified mRNAs suggests that the observed phenotype is largely independent of RNA folding. Thus, EU is a potential candidate for RNA‐based vaccines and therapeutics. Abstract : Activation of macrophages by exogenous mRNA : During transfection like electroporation and lipid nanoparticle uptake, mRNA is detected by immune surveillance receptors like toll‐like receptors‐3, −7 and −8. These receptors activate the secretion of type I interferons. In turn, autocrine signalling of these interferons activates inflammatory signalling pathways.